Big Data Analytics Framework for Smart Universities Implementations - Shamsuddin N.T.; Aziz N.I.A.; Cob Z.C.; Ghani N.L.A.; Drus S.M. (Springer Verlag, 2023)
Advanced Analytics; Behavioral research; Big data; Decision making; Internet of things; Smart city; Teaching; Critical component; Education domain; Internet of Things (IOT); Management decision-making; Smart grid; Smart technology; Smart universities; Teaching and learning; Data Analytics